Sistem Pendukung Keputusan Penentuan Calon Guru Honorer Di SMP Negeri 3 Kota Tambolaka Dengan Metode TOPSIS - Mere, Yohanes Isak (Jurnal Ilmiah Teknologi Informasi Asia, 2024)
To update the quality of schools, the importance of selecting honorary teacher candidates can be done by the school principal. Organizing the selection process for prospective honorary teachers is the main step for educational institutions to find more competent prospective honorary teachers. The teacher is a key element in the educational structure. However, due to the lack of an approach or system in the assessment process, the recruitment of prospective honorary teachers has not been successful. Therefore, it is considered important to build a decision support system that uses the TOPSIS method. This method makes it possible to choose the best option from the existing ones. By using this technique, the results will show prospective teachers who are more suitable to work in schools according to the standards set by educational institutions. Of the seven candidates who submitted their applications, 3 prospective honorary teachers were selected who met the requirements and matched the needs of educational institutions.